ANALISIS PENENTUAN KOMODITAS PERKEBUNAN UNGGULAN DI KECAMATAN NUHON KABUPATEN BANGGAI - Ambo Abdul Kadir Pakanyamong; Ratnawati Lisan; ismail Djamaluddin; Hertasning Yatim (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2026)
The development of the plantation subsector plays an important role in promoting regional economic growth, particularly in rural areas that rely heavily on agriculture. Identifying leading commodities is a strategic step in regional development planning to ensure more targeted and sustainable outcomes. This study aims to identify plantation commodities that serve as base sectors in Nuhon District, analyze the distribution of plantation commodities, and determine commodities with comparative and competitive advantages. The study uses secondary data in the form of plantation commodity production data for the period 2018–2022, obtained from the Central Bureau of Statistics (BPS), Agricultural Extension Center (BPP), and other relevant institutions. Data analysis was conducted using the Location Quotient (LQ) method to identify comparative advantages and the Shift Share Analysis (SSA) method to identify competitive advantages. The results show that coconut is the leading commodity in Nuhon District, as it has an LQ value greater than 1, a positive SSA value, and a wide distribution across most villages. Other commodities such as cocoa, cloves, coffee, and aren (sugar palm) also show potential as leading commodities; however, their level of advantage is still lower compared to coconut